2013
DOI: 10.1177/0194599813500754
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of the Combination of Intratympanic Methylprednisolone and Oral Steroid for Idiopathic Sudden Deafness

Abstract: We recommend that combination therapy can be considered as initial treatment especially for patients with severe hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 20 publications
0
53
0
3
Order By: Relevance
“…Of the two studies [22,23] comparing systemic, ITSI and combination therapy, one found that combination therapy was superior to systemic treatment alone (87.5 vs 44.4 %). As for the four remaining studies, three [24][25][26] found that combination therapy was superior to systemic therapy and one [27] favored ITSI over placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Of the two studies [22,23] comparing systemic, ITSI and combination therapy, one found that combination therapy was superior to systemic treatment alone (87.5 vs 44.4 %). As for the four remaining studies, three [24][25][26] found that combination therapy was superior to systemic therapy and one [27] favored ITSI over placebo.…”
Section: Resultsmentioning
confidence: 99%
“…The final logistic regression model suggests that IT-dexa may be a predictor of recovery after treatment in case of patients with SSNHL. Gundogan et al [13] also reported that combined therapy is more effective than oral steroid monotherapy in hearing outcome of patients with severe hearing loss. Additionally, Gunel et al [14] reported that 87.5% of patients who were initially treated with an intratympanic steroid showed full recovery (Siegel's criteria type 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of steroids in ISSNHL is still conflicting irrespective of the delivery method, recent previous studies found that combined steroid treatment (systemic steroid+ITS) provides better hearing recovery than systemic steroid alone. [6,7] Suzuki et al reported that systemic plus intratympanic steroid administration is more effective than systemic steroid plus HBO therapy. [19] It is believed that the diffusion of higher steroid concentration into cochlear fluids reduces inflammation in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data from three randomized controlled studies showed the benefit of combination therapy, especially in patients with mild-to-severe hearing loss. [6][7][8] In our institution, we have been preferring combination therapy as the initial management for ISSNHL and HBO therapy as salvage or adjuvant therapy after failure of combination therapy since 2013.…”
mentioning
confidence: 99%